(untitled) (Academicia Globe: Inderscience Research, 2023)
In the article, the author examines a number of problems related to the study of fine plastics and sculpture of small forms in the context of world art culture. One of the main problems is the problem of identification – the definition of fine plastics as a type of fine art or decorative and applied art.